The Influence of Compensation and Career Development Factors on Turnover Intention (Desire to Move to Work) Nurses at RSUD dr. HLM Baharuddin, M. Kes Raha - Sabarudin, Sabarudin; Nurlila, Ratna Umi; Asri, Andi (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction:This research was conducted at RSUD dr. HLM Baharuddin, M.Kes, Raha Regency. The purpose of this research was to determine and analyze the compensation and career development variables on the nurses' work desire variables, and to determine the variables that have a dominant influence on the nurses' work desire at RSUD dr. HLM Baharuddin, M.Kes. Method:The method used in this study uses a quantitative research method with a cross-sectional approach. The number of samples is 168 nurses working at RSUD dr. HLM Baharuddin, M.Kes which is determined through the Slovin sampling formula through a deliberate sampling technique. Analysis of research data using univariate analysis, multivariate analysis and multiple linear regression analysis. Result:The results of the study showed that there was a significant influence between the compensation received by nurses and the desire to change jobs, as well as career development having a significant influence on nurses' desire to change jobs. Conclusion: Although compensation does not have a significant effect on the desire of nurses to move, the hospital should pay attention to the welfare of nurses with contract status (non-civil servants) so that they continue to carry out their duties and responsibilities optimally.